Teaching Olympic values through outdoor experiential education: a case of belvedere technical teachers’ college, Zimbabwe - Zizhou, Fambisai (Πανεπιστήμιο Πελοποννήσου, 2018)
The purpose of this study was to explore the teaching of Olympic values through Kurt Hahn’s outdoor experiential education method. Since Zimbabwe gained its Independence in 1980 a number of policies and strategies were put in place to promote the teaching of values (unhu/ ubuntu) in order to arrest Moral decadence in youth. Noted constraints to the achievement of Moral inculcation included lack of research in this area, lack of mechanisms to enforce and monitor implementation of policies meant to promote teaching of values in schools, colleges and universities. This study aiming to improve the teaching and practice of values explored the possibility of teaching Olympic values through outdoor experiential method as a way to mitigate theerosion of Moral values in teacher education in Zimbabwe. The study aims to improve teaching practice standards and also positively improve behaviour of student teachers during and after teaching practice. It also seek to promote the use of outdoor experiential method as an effective method in inculcating teaching Olympic values and above all promote Olympic values education programs in Tertiary Colleges Institutions but Teachers’ Colleges in particular. Literature review hasbeen drone from Olympic values education programs done in Europe, America, Asia, Africa and Australia. The study qualitative survey methodology was adopted for this study. A purposive sampling technique was used to select a sample for this. The research targeted 200 students and 10 lecturers. However 35 students and 5 lecturers made the research possible. Data were gathered throughquestionnaires and these were complimented byfocus group discussions with students and individual interviews to lecturers. The findings revealed that Kurt Hahn’s outdoor experiential educationmethod is an effective tool in teaching Olympic values because it gives students an unforgettable and enjoyable experience in learning. This study noted that Olympic values education program can be successfully applied in teacher education to enhance the quality of teaching practice. The study also revealed that the inculcation of moral values students can be effectively donethrough adoption of Olympic values education programs in our educational system. Therefore the study recommends the following. An introduction ofOlympic Values Education Programsin Teachers’ Colleges. The adoption of Kurt Hahn’s outdoor experiential method in teaching Olympic values. An introduction of a support scheme to all Teachers’ Colleges who are involved in teaching Olympic values. Government and Non-Government Organisation to support Tertiary Institutions involved in teaching Olympic values.
Keywords: Olympic education - Curriculum - Zimbabwe; Olympic movement; Physical education and training - Curriculum - Zimbabwe; Ολυμπιακή παιδεία - Πρόγραμμα μαθημάτων - Ζιμπάμπουε; Ολυμπιακό κίνημα; Φυσική αγωγή και εκπαίδευση - Πρόγραμμα μαθημάτων - Ζιμπάμπουε; Olympic values; Experiential outdoor education; Moral values; Unhu/ ubuntu; Teaching